HUBUNGAN KECERDASAN SPIRITUAL DENGAN MASALAH MENTAL EMOSIONAL REMAJA - Sri Wahyuni; Jumaini Jumaini; Reni Zulfitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Spiritual intelligence is closely related to the tranquility of the soul which will also affect the emotional mentalcondition. This study aims to determine the relationship between spiritual intelligence and emotional mentalcondition of adolescents. This research was conducted at SMPN 18 Pekanbaru Riau utilizing the descriptivecorrelation research design using cross sectional approach. There were 71 respondents as the samples of theresearch. They were taken based on the inclusion criteria using simple random sampling technique. The measuringtools used were the spiritual intelligence questionnaire and the Strengths and Difficulties Questionnaire (SDQ). Theanalyses used were univariate analysis in order to know the frequency distribution and bivariate analysis usingalternative Fisher’s Exact Test. The results showed that among 53 respondents having high spiritual intelligence, 51respondents (96.2%) have abnormal emotional mental condition, and statistical test resulted in p value (1.000)>alpha (0.05). Therefore, it can be concluded that Ho failed to be rejected which means there was not anyrelationship between spiritual intelligence and emotional mental condition of adolescents. It is recommended thatparents and teachers should improve the emotional mental condition of the students at school.Keywords: Adolescents, EmotionalMental Problems, Spiritual Intelligence